A multidimensional analysis of the professional accountant’s ethical judgement and behavioural intentions - Subramanian, Kaveshan (My University, 2019)
Orientation: The professional accountant’s ability regarding ethical decision-making has come under increased scrutiny within recent times. This is particularly relevant within the South African accountancy environment given the recent accounting scandals that surfaced during 2017 and 2018. For professional accountants to achieve the goal of serving the public interest, they are required to have a mindset that fosters ethical-decision making. Research aim: The primary aim of this study was to explore the different factors which influence ethical judgement and behavioural intentions of professional accountants and to investigate which are significant factors which influence ethical-decision making. Ethical judgment involves the ability of the participant to recognise the seriousness of an ethical conflict whereas ethical behavioural intentions focus on the willingness of the participant to behave ethically. The secondary aim of the study was to explore the effect of demographical characteristics on ethical decision-making. Motivation for study: From a South African perspective, it is critical to ensure that professional bodies who are tasked with developing the accounting profession as well as serving the public interest gain a better understanding of the different factors which influence ethical judgment and behavioural intentions of professional accountants. Research approach and method: This study used a multidimensional ethics scale (MES) to measure the significant considerations of professional accountants when faced with an ethical dilemma. A quantitative research approach was followed and a questionnaire based upon the MES and three tax related ethical dilemmas was used to gather data. To address the research aims of the study, two research questions were answered through hypothesis testing which involved both descriptive and inferential statistical methods. Main results: The primary results indicated that factors such as morality, fairness, justice and acceptability to one’s family play the most significant role in influencing the ethical judgement of professional accountants. In addition, it was found that egoism which prioritises the long-term self-interest of the professional accountant significantly influences their ethical behavioural intentions. Lastly, the secondary results indicated that demographical characteristics such as rank and highest qualification attained by professional accountants play an important role in influencing the mind of the professional accountant when faced with an ethical dilemma. Application: This study contributes to the existing body of research involving ethical decision-making of professional accountants. This is an important topic in the current discourse on accounting and amongst accounting professionals. Furthermore, the results of this study can also form the basis of a mechanism for change within professional accounting bodies (PAO’s). The results of this study can be applied to assist in re-aligning continuous professional development (CPD) programmes. Based on the results, professional bodies can shift their focus in terms of CPD’s towards prioritising public interest as a key consideration for current and future accountants. To this end, PAO’s and higher education institutions can use this contribution when designing a new syllabus which addresses the issues that arise around ethical decision-making. Contributions: Key conclusions of this study contribute to the understanding of professional accountants’ ethical judgment and behavioural intentions. The topic under investigation is in direct response to calls for increased research on ethical judgement and behavioural intentions of professional accountants. The results also contribute towards a better understanding of the effects of gender, rank and professional qualifications on ethical decision-making.
A research report submitted to the Faculty of Commerce, Law and Management at the University of Witwatersrand in partial fulfilment of the requirements for the degree of Master of Commerce, February 2019
Keywords: UCTD; Ethics; Ethical judgement and behavioural intentions; Multidimensional ethics scale; Professional accountant; Accountant--Professional ethics--South Africa; Accounting--South Africa; SDG-8: Decent work and economic growth